Inter-Religious Social Prejudice among Indonesian Muslim Students - Nashori, Fuad; Nurjannah, Nurjannah; Diana, Raden Rachmy; Faraz, Faraz; Khairunnisa, Nadea Zulfa; Muwaga, Musa (Program Studi Ilmu Agama Islam Program Magister, Universitas Islam Indonesia, 2024)
Indonesia is a nation marked by extensive diversity encompassing a myriad of languages, ethnicities, and religious affiliations. While some studies support the positive implications associated with this diversity, others argue that it harbors the potential for social discord, particularly within distinct religious communities. This research aims to scrutinize the dynamics of mature religious sentiment and Islamic knowledge concerning Muslim-Christian relations, specifically exploring their impact on social prejudice among Muslim students, who constitute the majority and hold prejudicial views towards Christians. The investigation was conducted among Muslim students aged 18-22 in Yogyakarta, Indonesia (N = 254). Employing the structural equation model (SEM) technique for analysis, the findings reveal that mature religious sentiment exerts a direct influence on social prejudice, both independently and mediated through the agreeableness trait. Additionally, Islamic knowledge pertaining to the Muslim-Christian relationship directly influences social prejudice without the intermediary of agreeableness.